The Acculturation Toolkit: An Orientation for Pediatric International Medical Graduates Transitioning to the United States Medical System - Cynthia Katz; Michelle Barnes; Amanda Osta; Ingrid Walker-Descartes (Association of American Medical Colleges, 2020)
Introduction International medical graduates (IMGs) consistently contribute to the US physician workforce. In fact, 25% of practicing pediatricians in the US are IMGs, highlighting the needs of IMG trainees. IMGs face unique challenges with acculturation compared to their peers due to unfamiliarity with the US medical system, especially the dynamics around patient-centered care. The literature supports the need for formal acculturation curricula. Methods A cohort of program directors who train pediatric IMGs coupled findings from the literature with local themes from IMG focus groups to identify topics for an acculturation curriculum. Three small-group workshops utilized didactics, discussion, and role-play to cover topics related to patient-centered care, challenging communication with patients, complex psychosocial histories, and health literacy. The pilot was modified based on feedback and to enhance generalizability. The resulting four-module curriculum with presentations and supplemental materials is presented here. Results After a 3-year pilot with 36 PGY 1 trainees, postcurriculum surveys reported 8.1 out of 10 in workshop satisfaction, plus increased knowledge and skills related to patient-centered care and communication with patients. Role-plays were the favorite activity. A 1-year follow-up survey reported the workshops to be influential on satisfaction with patient relationships and easing transition to residency. Discussion A pilot acculturation curriculum addressing needs of pediatric IMG trainees was well received by participants and improved their comfort level in addressing challenging patient-communication scenarios. Pediatric programs that train IMGs can incorporate this curriculum to aid residents' transition to clinical practice in the US.